Inside dreamweaver 4 - Yerks, Anne-Marie.; Pickett, John. ([S.l.] : Waite Group Press, 2001)
Inside Dreamweaver 4 is a tutorial reference that combines knowledgeable explanation with insightful learning activities to engage readers. The end result is a more in-depth knowledge of the software and how it can provide solutions for the user in the work environment. Inside Dreamweaver 4 assumes that readers have a basic understanding of the software and are looking for solutions to the problems they have incurred. As a result, this book will not dwell on information that is readily available in the software documentation. A brief section introduces Dreamweaver and HTML. After that, the authors present the new features of Dreamweaver 4 and discuss customizing the software before delving into such topics as: HTML Creation Fundamentals, Advanced Document Structuring, Site Management, Rich Media Usage, and Extensibility.